IMPLEMENTASI MODEL PEMBELAJARAN PROJECT-BASED LEARNING (PJBL) DALAM PENGEMBANGAN BERPIKIR KRITIS - Mardatillah, Dinah; Dadan Setiawan (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2025)
This study aims to analyse the effectiveness of Project-Based Learning (PjBL) learning model in improving critical thinking skills of elementary school students. The research method used a quasi-experimental design with one group pretest- posttest, involving 23 students of class III-A SDIT Al-Falah as samples. The research instruments consisted of tests and assessment rubrics that measured critical thinking indicators, such as problem solving, analysis, and evaluation. The results showed a significant increase in students' critical thinking skills, with the posttest average score reaching 100 compared to the pretest of 63.26. The t-test analysis resulted in a significance value of 0.015 (<0.05), proving that the PjBL model had a positive effect on improving critical thinking skills. However, the evaluation aspect still needs further strengthening. Effective implementation of PjBL requires teacher training, a supportive learning environment, and comprehensive evaluation. This research contributes to the development of innovative learning methods to improve 21st century skills at the primary education level.